행정검시제도 개선방안 - 김헌진(Heon-Jin Kim) (한국콘텐츠학회 논문지, 12(2), 2012)
Current Administrative Death investigation system is have many problems. Almost local governor don't exercise about administrative death investigation authority. Thus, prosecutors have to many decisions about judicial death investigation authority. Consequently, these vicious cycle is repeated. There is not clear regulations about scope for judicial death investigation. Discussed in this paper improve the Administrative Death investigation system are as follows : First, the uniform act of death investigation is have to legislated. Second, the scope for death investigation is clearly legalized. Medical examiner is must administrative death investigation according to the law. Also prosecutor can order to judicial autopsy to medic examiner. Third, Administrative Death investigation rules should be clarified. Introduce a Medical Examiner System Korean Administrative Death Investigation system centered on prosecutor and judicature who are not a specialist in pathology or forensic medicine. Lacking in professional understanding cause less accuracy of Administrative Death Investigation. To overcome limitations and problems of our Administrative Death Investigation system is suggested to introduce a Medical Examiner system. 현행 행정검시제도는 몇 가지 문제점을 갖고 있다. 행정검시권자는 자치단체장이지만 실제로는 대부분 형사소송법상 변사체로 처리되어 검사의 지휘로 사법검시가 이루어지고 있다. 또한 검시대상이 분명하게 규정되어 있지 않아 제대로 죽음의 원인이 밝혀지지 않는 이른바 의문사의 문제도 사회적인 현안으로 자리하고 있다. 이 논문에서는 행정검시제도 개선방안으로 첫째 검시에 관한 통일적인 법률체계의 정비가 필요하며 둘째 검시대상을 명확히 함으로써 법의관은 법률에 규정된 사체에 대한 검시책임을 지며, 그 결과 범죄가능성이 있는 경우 수사기관에 통보할 의무를 부여하고, 셋째 수사기관도 검시가 필요한 사체에 대해 법의관에게 검시를 요구해야 한다. 넷째, 사망원인 조사에 전문성이 부족하면 정확성이 떨어지므로 의학적 전문지식이 있는 법의병리전문의 또는 법의관이 검시의 주체가 되어야 할 것이다. 이 논문에서는 우리나라의 행정검시제도의 한계와 문제를 극복하기 위해서 행정검시 개선방안을 소개했다.